Changes in soil phosphorus (P) fractions and P bioavailability after 10 years of continuous P fertilization - Biassoni, María Micaela; Vivas, Hugo; Gutierrez Boem, Flavio Hernán; Salvagiotti, Fernando (Elsevier, 2023)
Phosphorus fertilization modify soil P fractions differing in availability, but little is known about bioavailability of these pools for the crops when increasing P fertilizer rates in the medium term. Our objectives were to evaluate: i) changes in Bray-1 P content (extracted with 0,03 M NH4F and 0,1 M HCl) and soil P fractions as estimated by physical (Cambardella and Elliot method, POM-P) and chemical fractionation (Hedley method), ii) the relationship between these fractions and P bioavailability quantified in a test crop, and iii) the interaction with sulfur (S) fertilization after 10 years of continuous P and S fertilization. Soil samples were taken after 10 years in an experiment that followed a maize - full season-soybean - double-cropped wheat /soybean sequence that received P and S fertilization when cereals were sown. Treatments consisted of a factorial combination of three P rates (0, 20, and 40 kg P ha−1) and four S rates (0, 12, 24, and 36 kg S ha−1) applied to cereals from 2000 to 2010. After that, a maize used as a test crop was sown and P uptake was considered as bioavailable P. Soil samples were taken before sowing the test crop, and P in soil was fractionated chemically by the Hedley method and physically by wet sieving. After 10 years, when P fertilizer was not applied, soil Bray-1 P decreased 50 % respect to the initial P values, and increased up to 2.3 times when evaluating the highest P fertilizer rate. P fertilization did not change in POM-P. P soil labile (NaHCO3-Pi) and moderately labile (NaOH- Pi and HCl 1 M- Pi) inorganic fractions increased 83 %, 50 %, and 22 % in response to P addition, representing an increase of 4.2, 4.9, and 4.5 mg kg−1 of these fractions per 100 kg of applied P. Likewise, these fractions were related with P uptake in the maize test crop with 1.6, 1.5, and 1 kg of P uptake ha−1 in mg kg−1 increase in each of these fractions, respectively. Then, these fractions may be responsible for the legacy-P after 10 years of continuous fertilization in a Luvic Phaeozem of the Pampas region.